An overview of numerical methodologies for durability assessment of vehicle and transport structures. (30th June 2010) - Wannenburg, Johann; Heyns, P. Stephan
Numerical methodologies for assessing the durability of vehicle and transport structures are reviewed. These methodologies are mapped in terms of a framework that emphasises the relationships among them. Load inputs are obtained from either measurements or simulation. These loads are used as inputs into stress analyses, which may be either quasi-static or dynamic, and either in the time domain or in the frequency domain. The outputs of these analyses can be then used in fatigue analyses. The advantages and disadvantages of each method are analysed. A case study is described to demonstrate the insights gained from the mapping framework.